The Relationship Level Of Knowledge And Attitude Of Mothers During Pregnancy To Mother's Behavior At The Time Of HIV Pretest In The HIV TKIP Program At Puskesmas Kotabaru 2023 - Asidah Ariyati; Nanik Yuliwati (Pusat Riset dan Inovasi Nasional, 2023)
Backgrounds : Based on the guidelines for Integrated Ante Natal Care pregnancy checks issued by the Minister of Health at every level of MCH services, health workers in health care facilities are required to test all pregnant women for HIV, syphilis and hepatitis B at least once as part of routine laboratory examinations during pregnancy. antenatal checks at visit 1 (K1) until just before delivery. Research objectives : To determine the relationship between the level of knowledge and attitudes of pregnant women with their behavior towards the HIV pretest at the Kota Baru Health Center. Type of research : Research conducted in June. The sample in this study was 60 samples in the Kota Baru Health Center area. This study uses a questionnaire and checklist with a quantitative approach method with a cross-sectional research design. Total sampling technique. The results of the study : The distribution is known from 60 respondents, the majority of respondents have good knowledge about preventing mother to child transmission as many as 47 people 78.3%, the less good there are 13 people 21.7% distribution of attitudes from 60 respondents, the negative value is less than 20 regarding prevention of mother to child transmission, namely as many as 12 or 20.0% of respondents, while positive values ​​of more than 20 were 48 students or 80.0% of distribution of the behavior from 60 respondents, who participated in preventing mother to child transmission, namely as many as 41 68.3% of respondents, who did not participate in preventing mother-to-child transmission, namely 19 or 31.7% of respondents. Based on the results of the chi-square statistical test, it is obtained that the p value = 0.002 is smaller than the value α = 0.005. Research conclusion : There is a significant relationship between knowledge and the use of HIV testing at the Kota Baru Health Center, while the results of the chi-square statistical test obtained p=0.006, meaning that there is an attitude relationship between knowledge and the use of HIV testing at the Baru City Health Center.